2011
DOI: 10.1080/02640414.2011.552113
|View full text |Cite
|
Sign up to set email alerts
|

Markers of isometric training intensity and reductions in resting blood pressure

Abstract: In this study, we examined the correlations between selected markers of isometric training intensity and subsequent reductions in resting blood pressure. Thirteen participants performed a discontinuous incremental isometric exercise test to volitional exhaustion at which point mean torque for the final 2-min stage (2min-torque(peak)) and peak heart rate peak (HR(peak)) were identified. Also, during 4 weeks of training (3 sessions per week, comprising 4 × 2 min bilateral leg isometric exercise at 95% HR(peak)),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Baross et al [32] reported significant reductions in SBP (−11 mmHg) and MAP (−5 mmHg) following isometric bilateral-leg training at relatively low intensities (approximately 14% MVC). However, the studies of Devereux et al [16] and Baross et al [32] used much longer periods of exercise, than we used in the present study; therefore the training stimulus is likely to have been much greater. In the present study training was performed 4 times per week, whereas most previous isometric training studies have used 3 times per week, and this may have contributed to our significant findings.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Baross et al [32] reported significant reductions in SBP (−11 mmHg) and MAP (−5 mmHg) following isometric bilateral-leg training at relatively low intensities (approximately 14% MVC). However, the studies of Devereux et al [16] and Baross et al [32] used much longer periods of exercise, than we used in the present study; therefore the training stimulus is likely to have been much greater. In the present study training was performed 4 times per week, whereas most previous isometric training studies have used 3 times per week, and this may have contributed to our significant findings.…”
Section: Discussionmentioning
confidence: 87%
“…There is some evidence that brief, and low-intensity, isometric training programmes can induce reductions in resting blood pressure. For example, Devereux et al [16] reported significant reductions in SBP (−5 mmHg) and MAP (−3 mmHg) following only 4 weeks of isometric bilateral-leg training at an exercise intensity that equated to approximately 20% MVC. Baross et al [32] reported significant reductions in SBP (−11 mmHg) and MAP (−5 mmHg) following isometric bilateral-leg training at relatively low intensities (approximately 14% MVC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies were included in our analysis, [16][17][18][19][20][21][22][23][24] with a total of 223 patients (Supplemental Table 1, available online at http://www.mayo clinicproceedings.org). Six studies used handgrip, and 3 studies used leg exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Isometric training was performed in the same way as detailed previously [4, 21]. Briefly, participants performed an MVC test and then an incremental isometric exercise test.…”
Section: Methodsmentioning
confidence: 99%